Prospective Cardiovascular Genetics Evaluation in Spontaneous Coronary Artery Dissection - Kaadan, M Ihsan; MacDonald, Carolyn; Ponzini, Francesca; Duran, Jessica; Newell, Kelsey; Pitler, Linda; Lin, Angela; Weinberg, Ido; Wood, Malissa J; Lindsay, Mark E (Circulation. Genomic and precision medicine, 2018)
Previous studies describing genetics evaluation in spontaneous coronary artery dissection (SCAD) have been retrospective in nature or presented as single case reports. As part of a dedicated clinical program, we evaluated patients in cardiovascular genetics clinic to determine the role of genetically triggered vascular disease and genetic testing in SCAD. Patient data were entered prospectively into the Massachusetts General Hospital SCAD registry database from July 2013 to September 2017. Clinically indicated genetic testing was conducted based on patient imaging, family history, physical examination, and patient preference. Of the 107 patients enrolled in the registry, 73 underwent cardiovascular genetics evaluation at our center (average age, 45.3±9.4 years; 85.3% female), and genetic testing was performed for 44 patients. A family history of aneurysm or dissection was not a prevalent feature in the study population, and only 1 patient had a family history of SCAD. Six patients (8.2%) had identifiable genetically triggered vascular disease: 3 with vascular Ehlers-Danlos syndrome ( ), 1 with Nail-patella syndrome ( ), 1 with autosomal dominant polycystic kidney disease ( ), and 1 with Loeys-Dietz syndrome ( ). None of these 6 had radiographic evidence of fibromuscular dysplasia. In this series, 8.2% of the SCAD patients evaluated had a molecularly identifiable disorder associated with vascular disease. The most common diagnosis was vascular Ehlers-Danlos syndrome. Patients with positive gene testing were significantly younger at the time of their first SCAD event. A low threshold for genetic testing should be considered in patients with SCAD.